Health disparity at the intersection of religion and caste: Evidence from India - Biplab Kumar Datta; Shriya Thakkar (Dialogues in Health)
Objective: The provisions and recognition of Schedule Castes (SCs), the constitutional term for the Dalits in India, have been exclusively extended to Hindus, Buddhists, and Sikhs (HBS). Omission of Dalit Muslims and Christians (MC) from the SC category stripped them of the affirmative action benefits tied with the SC status. This study aimed to explore how such differential treatment might play a role in differential health outcomes in Dalit women in India. Methods: Drawing data on 177,346 Dalit women, aged 20 to 49 years, from two successive nationally representative surveys, we assessed the differential likelihood of hypertension and diabetes, between MC- and HBS- Dalit women. Accounting for birth cohort-, survey wave-, and state of residence- fixed effects, along with socioeconomic conditions and cardiometabolic risk factors, we obtained adjusted odds of having hypertension and diabetes in MC women. To check the validity of our results, we conducted similar analyses using data on 170,889 Scheduled Tribe (ST) women, another marginalized group, whose ST-status recognition were not tied to religion. Results: We found that Dalit MC women were 1.13 (95% CI: 1.03–1.25) and 1.19 (95% CI: 1.05–1.36) times more likely to have hypertension and diabetes, respectively, compared to Dalit HBS women. Conversely, no statistically significant differential likelihood of these conditions was observed between MC and HBS women in the ST sample. Conclusion: Our investigation thus, indicated a potential link at the crossroads of religion and caste that may contribute to the health disparities among marginalized women in India.